EVALUATION OF THE EFFICACY OF NEWCASTLE DISEASE (LASOTA) LIVE VACCINES SOLD IN JOS, PLATEAU STATE, NIGERIA - Richard, Akele Y.; Mirabeau, Tatfeng Y.; Tony, Ojiezeh I.; Solomon, Chollom C.; Samsom, Enitan S.; Ayodeji, Olayanju O. (European Scientific Journal, ESJ, 2014)
Introduction: Newcastle Disease is a highly contagious and commonly fatal viral poultry disease. The study was carried out to determine the efficacy of Newcastle Disease (NDV) vaccines sold at open market in Jos. Materials and methods: Five commonly used brands of ND LaSota live vaccines were used for the study. Haemagglutination test (HA) and Egg Infective Dose (EID50) was carried out on the vaccines.Sixty (60) day-old unvaccinated white leghorn broilers were distributed into 6 groups n=10 and allowed to acclimatize for 6 days. Groups 1-5 were vaccinated intraoculally with vaccines coded A - E respectively, while group 6 was not vaccinated (control group). They were bled on days 7, 14, 21 and 28 post vaccinations (PV) for antibody titration using standard methods. They were challenged